Gender and belief factors on attitude towards Social and Environmental Accounting (SEA) / Salina Abdullah and Loo Ern Chen - Abdullah, Salina; Loo, Ern Chen (Research Management Institute (RMI), 2009)
Research on social and environmental accounting (SEA) has mainly concentrated on disclosure of SEA by corporate bodies, where investigations on ones attitude towards SEA are rarely discussed. SEA is a medium that develops relationships between business and society, community and nature. In addition, SEA involves a concept of sustain ability; where natural resources need to be sustained for the needs of future generations (Alhabshi et al., 2003). SEA also tries to recognise the role of accounting in sustainable development and the use of environmental resources. There are arguments that the young generations today are not fully aware of preserving these natural resources as well as handling social and environmental issues wisely. This perhaps link closely to their belief and cultural background. Hence, this paper examines the influence of gender and belief factors on the undergraduate students’ attitude towards SEA. Four dimensions of belief (fixed ability, quick learning, simple knowledge and certain knowledge) proposed by Schommer (2005) were adapted to analyse how belief factors have influence on their attitude towards SEA. An independent sample t-test was used to examine the relationship between gender and students’ attitude towards SEA. Spearmen’s correlation was employed to show the relationship between belief and attitude towards SEA. The results revealed that gender differences did not show influences on their attitude towards SEA. It was found that there is a significant relationship between belief and students’ attitude towards SEA. Students who believe on the importance of SEA tend to report positive attitude towards SEA. Perhaps findings of this study may provide some information on the SEA education and further be incorporated in the syllabus.